Education on Preparing Annual Tax Returns with E-Filling Mechanism at LMATS Consulting - Nuning Indah Pratiwi; Ni Komang Ayu Santika Putri; Wahyu Indra Satria (LPPM UIKA Bogor, 2023)
Taxes are a source of state revenue to finance all government spending in general. The Indonesian state views taxation as the role and obligation of citizens in financing development. The goal is to increase awareness and a sense of responsibility in society. Taxes are used to regulate or implement government policies in the economic field. To make it easier for the public to fulfill their tax obligations as taxpayers, DJP has also improved its services by establishing a program for reporting and paying taxes. This program is an online program that is used by the majority of Indonesian people, the Director General of Taxes launched an update, namely access to electronic Annual SPT reporting via e-filling. E-filling is expected to be effective and appropriate as a means of electronic tax reporting that can fulfill tax obligations. As for the report that will be raised in this discussion, the author takes the title